Do consumers understand health claims on extra-virgin olive oil?. (May 2021) - Lombardi, Alessia; Carlucci, Domenico; Cavallo, Carla; De Gennaro, Bernardo; Del Giudice, Teresa; Giannoccaro, Giacomo; Paparella, Antonio; Roselli, Luigi; Vecchio, Riccardo; Cicia, Gianni
Graphical abstract: Highlights: Understanding health claims on food label is difficult for many consumers. Consumer understanding of the health claims applicable to olive oil was measured. An Olive Oil Health Claims Understanding index was constructed. Low understanding of the health claims applicable to olive oil was detected. Drivers of consumers understanding were identified and measured. Abstract: Health claims have been introduced in food labelling to support consumers' awareness of healthy food choices and to enhance a healthy diet. Even though many countries around the world have developed legislation and guidelines to regulate the introduction of health claims on food labels, there is the evidence that many consumers do not understand the meaning of these claims. This study analyses whether Italian consumers really understand authorized health claims on extra-virgin olive oil and what are the drivers of such understanding. An Olive Oil Health Claims Understanding index was constructed and embedded in a structured questionnaire, which was then administered to a representative sample of Italian household members who are responsible for food shopping (N = 1, 030). Results from the survey showed that only 36% of the respondents understood the meaning of the authorized health claims on extra-virgin olive oil. Moreover, the findings confirmed that the understanding of health claims is related to socio-demographic, personal and psychographic characteristics of consumers, as well as to their attitudes toward using food as medicine. Outcomes also proved the central role of nutrition knowledge in affecting understanding of health claims.